2020
DOI: 10.1111/ocr.12368
|View full text |Cite
|
Sign up to set email alerts
|

Palatal volume estimation in operated unilateral and bilateral cleft lip and palate subjects using digital study models

Abstract: Cleft lip and palate (CLP) is the most common birth defect affecting the face with an overall incidence of 1 out of 700 live births. The interdisciplinary treatment required in the treatment of cleft patients presents a challenge to healthcare professionals throughout the world. 1 The operated cleft lip and palate patients show a reduction in maxillary growth which is evident by midface retrusion 2 and anterior crossbite. 3 The growth inhibitory effects also extend to transverse

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 30 publications
1
15
1
Order By: Relevance
“…The palatal volume in operated cleft lip and palate patients both UCLP and BCLP, was evaluated using digital models. [ 17 ] The results of the study showed significantly lesser palatal volume in cleft patients compared to non-cleft controls. [ 18 ] The palatal volume in operated cleft lip and palate patients, both UCLP and BCLP was estimated using digital models and palatal volume in cleft patientswas found to be smaller compared to non-cleft controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The palatal volume in operated cleft lip and palate patients both UCLP and BCLP, was evaluated using digital models. [ 17 ] The results of the study showed significantly lesser palatal volume in cleft patients compared to non-cleft controls. [ 18 ] The palatal volume in operated cleft lip and palate patients, both UCLP and BCLP was estimated using digital models and palatal volume in cleft patientswas found to be smaller compared to non-cleft controls.…”
Section: Discussionmentioning
confidence: 99%
“…The recent studies[ 17 18 ] estimated the palatal area and volume in patients with cleft deformity using digital models and found that measurements were smaller as compared to normal control. The palatal area in nonsyndromic and unoperated CLP patients evaluated the intrinsic deficiency of maxillary growth and found that the intrinsic deficiency was also a contributing factor for maxillary hypoplasia.…”
Section: Introductionmentioning
confidence: 99%
“…10 Few studies analyzed the volume on dental casts of individuals with cleft lip and palate through different methodologies. [12][13][14][15][16] Some studies analyzed the palate volume of children by marking the gingival margin and a plane tangent to the primary and/or permanent teeth, posteriorly, [12][13][14] while others evaluated through the segmented areas of the dental arches. 15,16 In this study, we employed the methodology described by Pucciarelli et al 8 because of the proven accuracy and repeatability of the volumetric analysis à Statistically significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the critical role played by the amount of bone required for reconstruction of the bone defect, rather than using objective criteria, surgeons mostly determine the amount of graft on the basis of their experience, potentially resulting in either superfluous or scarce graft harvest. Heiser et al (2004) were the first to attempt measurement of palatal volume, and this was done indirectly by weight correlation [ 24 ]. According to Quereshy et al, objective criteria to estimate the amount of graft were landmarks and linear calculations, corresponding to the cleft width, height, and facial-palatal length.…”
Section: Discussionmentioning
confidence: 99%